Figures du lycanthrope à l’âge baroque - Édith Girval (Etudes Epistémè)
The image of the werewolf, whose roots can be found in Pline’s or Petronius’ tales of metamorphosis, undergoes an intriguing reinterpretation in the Baroque era under the name of “lycanthrope”. This new figure of the werewolf does not belong to the realm of magic or witchcraft – its metamorphosis, that is no more physical, but psychological, is explained by medicine and science. In the writings of Cervantes, Burton, and especially Webster, this half-human and half-wolf figure transcends its mythical and demonic werewolf ancestors.